A Study on the Factors that Influence Trading Success among Individual Equity Derivative Traders in Bengaluru City - Deepika; Sudhamathi (Ushus Journal of Business Management, 2022)
Derivative trading triggers extensive public attention because it is time and again considered an easy way to make money. This study aims at identifying the variables that influence trading success in the equity F&O market by thoroughly reviewing the literature and then condensing these variables into a few factors or components using Principle Component Analysis. Using PCA, 39 variables were grouped into components such as knowledge, trading behaviour, risk management skills, emotional intelligence, tech-savviness, personal habits and social interaction. These seven components explained 71.747% of the total variance.